2021
DOI: 10.1002/pld3.310
|View full text |Cite
|
Sign up to set email alerts
|

Nodal root diameter and node number in maize (Zea mays L.) interact to influence plant growth under nitrogen stress

Abstract: Developing stress-tolerant, resource-efficient crops is a key strategy for addressing the challenges of climate change, global food security, and land degradation (Blum & Jordan, 1985; Hunter et al., 2017; Mickelbart et al., 2015). Maize is a critical global crop, cultivated for food, fuel, and industrial uses (FAO, 2018). In intensive agriculture systems, nitrogen (N) fertilizers are over-applied to maximize grain yield, yet over half of the applied nitrate leaches beyond the root zone and pollutes waterways,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The percentage of roots with root hairs was not affected by the amounts of applied N (N0 and N227), but N0 led to a decrease in both root number and root hair length in all maize genotypes. Schneider et al (2021) found that maize lines with few-thick nodal roots had smaller total axial root lengths in N0, while lines with many-thin developed a greater total axial root length in N0. The phenotype of fewer, thicker nodal roots was associated with deeper root distribution and resulted in an increased shoot growth under N deficiency.…”
Section: Root Diameter Root Diameter Distribution and Specific Root L...mentioning
confidence: 89%
“…The percentage of roots with root hairs was not affected by the amounts of applied N (N0 and N227), but N0 led to a decrease in both root number and root hair length in all maize genotypes. Schneider et al (2021) found that maize lines with few-thick nodal roots had smaller total axial root lengths in N0, while lines with many-thin developed a greater total axial root length in N0. The phenotype of fewer, thicker nodal roots was associated with deeper root distribution and resulted in an increased shoot growth under N deficiency.…”
Section: Root Diameter Root Diameter Distribution and Specific Root L...mentioning
confidence: 89%
“…The results suggest ethylene‐induced root thickening may be node‐specific as well as genetically variable. Recent studies have demonstrated root anatomy and architectural traits are node specific and may be under distinct genetic control (Schneider et al, 2021 ; Schneider et al, 2021 ; Schneider, Yang, Brown, & Lynch, 2021 ; Yang, Schneider, Brown, & Lynch, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These observations align with the hypothesized advantages of the ‘steep, deep, cheap’ ideotype for improved N capture proposed by Lynch (2013) , where exploration of deeper soil domains improves the acquisition of mobile resources such as nitrate. The fitness benefits of this foraging strategy have also been demonstrated in vivo where maize genotypes that produced few, thick nodal roots had a deeper distribution of root length and greater shoot growth under N deficit compared with genotypes that produced many, thin nodal roots ( Schneider et al , 2021 b ). Compaction can lead to decreased, constant or even increased root numbers ( Bushamuka and Zobel, 1998 ; Grzesiak et al , 2014 ; Colombi and Walter, 2016 ).…”
Section: Discussionmentioning
confidence: 98%